Expression analysis of cytokines IL-5, IL-6, IL-8, IL-17 and VEGF in breast cancer patients - Liu, Gang; Chen, Xiang-Ting; Zhang, Hao; Chen, Xin (Frontiers in Oncology, 2022)
Abstract Objective: To investigate the relationship between changes in peripheral blood vascular endothelial growth factor (VEGF), interleukin-5 (IL-5), interleukin-6 (IL-6), interleukin-8 (IL-8) and interleukin-17 (IL-17) concentrations in breast cancer patients and their significance and clinical value in breast cancer staging and invasive metastasis. Methods: From September 2021 to April 2022, 60 breast cancer patients from Chongqing Medical University Hospital No. 2022 were enrolled in the breast breast cancer surgery group, while 30 patients with benign breast disease were enrolled in the control group during the same period. Venous blood samples were collected at admission and 1 week after surgery to determine the expression of these factors in serum.. Statistical methods such as Wilcoxon test and Spearman correlation analysis were used to analyze the relationship between the above factors and the clinicopathological characteristics of the patients. Results: By analyzing data from patients with benign and malignant breast tumors, an association was found with serum levels of IL-6, IL-17 and VEGF. Their respective areas under the operating characteristic curve were 0.649, 0.734 and 0.656 (P < 0.05). There were significant differences in the cytokine expression levels of IL-17 and VEGF in different molecular typing (P values were 0.008 and 0.040, respectively). The expression levels of IL-17 and VEGF were higher in HER-2 receptor-positive and triple-negative patients than in hormone receptor-positive patients (P < 0.05). Also, no significant correlation was found between the various cytokines mentioned in the article and breast cancer lymph node metastasis and Tumor Node Metastasis stage (TNM stage). In addition, in the breast cancer surgery group, postoperative VEGF levels were lower (P < 0.05) and IL-6 levels were higher (P < 0.05) compared to preoperative levels. Conclusions: Serum IL-6, IL-17, and VEGF are strongly associated with breast cancer development and can be used as a reference indicators for breast cancer diagnosis. In addition, post-operative VEGF levels decreases and IL-6 levels increases compared to pre-operative levels, which can also be used as an a postoperative follow-up indicator. In contrast, IL-5 and IL-8 have not found to be significantly associated with breast cancer patients in this study, which requires further study.